Performance Assessment of Screw Piles Embedded in Soft Clay - Omar Kareem Ali; Hassan O. Abbas (Civil Engineering Journal, 2019)
Screw piles are widely used in a variety engineering applications supplying stability against compression, overturning moment, uplift tension, and horizontal loads. Screw pile is a famous solution for support light structures, roads and rail signs which have relatively low-capacity foundation. In this study, the behavior of circular (10) mm solid screw pile models embedded in a bed of soft clay soil covering a layer of sandy soil has been studied. The 200 mm thick sand layer was compacted in a steel container with a diameter of 300 mm into four sublayers. The sandy soil layer was compacted at a relative density of 70%. The 300 mm thick soft clay soil bed with Cu (30) kPa was compacted in six sub-layers on the sandy bottom layer. Model tests are carried out with screw piles with a length of 300 mm, 350 mm and 400 mm and a helix diameter of 30 mm. Also, single and double helix and different S/Dh ratio were used for these piles and a comparative study between screw piles and ordinary piles (without helices) is accomplished. This study revealed that introducing screw pile of double helix increases its bearing capacity in soft clay soil by up to a (4-8) % as compared to a single helix screw pile. The results showed that the behavior of screw pile essentially depends on the geometric properties of the pile. According to the achievements, compressive load capacity of screw piles depends on embedded length, spacing ratio (S/Dh) and number of helical plates.